Inquiry-based learning for multidisciplinary programs a conceptual and practical resource for educators - Blessinger, Patrick; Carfora, John M. (Bingley, U.K. : Emerald, 2015)
Inquiry-based learning (IBL) is a learner-centered, active learning environment where learning is cultivated by a process of inquiry owned by the learner. It has roots in a constructivist educational philosophy and is oriented around three components: 1) exploration and discovery (e.g. problem-based learning, open meaning-making), 2) authentic investigations using contextualized learning (e.g. field and case studies), and 3) research-based approach (e.g. research-based learning, project-based learning) IBL begins with an authentic and contextualized problem scenario where learners identify their own issues and questions and the teacher serves as guide in the learning process. It encourages self-regulated learning because the responsibility is on learners to determine issues and research questions and the resources they need to address them. This way learning occurs across all learning domains. This volume covers the issues and concepts of how IBL can be applied to multidisciplinary programs. It serves as a conceptual and practical resource and guide for educators, offering practical examples of IBL in action and diverse strategies on how to implement it in different contexts.
Innovative approaches in teaching and learning : an introduction to inquiry-based learning for multidisciplinary programs / Patrick Blessinger, John M. Carfora -- The problem-oriented project work (PPL) alternative in self-directed higher education / Anders Siig Andersen, Simon B. Heilesen -- Critically examining inquiry-based learning : John Dewey in theory, history, and practice / William E. Herman, Michele R. Pinard -- Folknography : inquiry-based learning and qualitative research / David M. Lucas, Charles W. Jarrett -- Resonance-based inquiry : an epistemological approach to Indian studies / Nicholas J. Shudak -- Developing an interdisciplinary inquiry course on global justice : an inquiry-informed, cross-campus, collaborative approach / Beth Marquis, Vivian Tam -- Inquiry-based learning as foundational pedagogical tool for critical examination of social justice in theory and action / Alia Sheety, Nicholas Rademacher -- Inquiry-based learning as a gateway for exploration into human environmental conflicts / Becky Boesch -- Developing digital student selves : using an inquiry-based approach to explore digital confidence in creative learning / Vic Boyd -- A master's level research methods class : a practice example of inquiry-based learning / Kathleen B. Duncan, Teresa Martinelli-Lee -- Problem finding through design thinking in education / Gavin Melles ... [et al.] -- Connecting inquiry-based learning with collaborative work in online education / Albert Sangrà, Mercedes González-Sanmamed, Montse Guitert -- Using inquiry-based learning outside of the classroom : how opportunities for effective practice can animate course-based learning / Michelle Bata, Amy Whitney -- Chaos and order : scaffolding students' exploration during inquiry-based learning / Debra L. Gilchrist, April D. Cunningham -- The Life Arts Project : application of an inquiry based learning model for adult learners / Darryl E. Jones -- Reconfiguring affective, conative and cognitive outcomes in IBL : a multi-disciplinary case study / Mary Dickinson, David Dickinson -- Enhancing inquiry-based online teaching and learning : integrating interactive technology tools to scaffold inquiry-based learning / Kathy-ann Daniel-Gittens, Tina Calandrino -- Multidisciplinary online inquiry-based coursework : a practical "first steps" guide / Tanya D. Whitehead -- Inquiry in the coaching experience : reflective strategies for transformative change / Greg Latemore -- Classroom without walls : inquiry-based pedagogies and intercultural competence development via service-learning / Christine E. Poteau.
Includes indexes.
Print version record
Keywords: Education; Study & learning skills: general; Inquiry-based learning; Thought and thinking; Critical thinking